Thromboprophylaxis for recurrent miscarriage in women with or without thrombophilia - Visser, Jantien; Ulander, Veli-Matti; Helmerhorst, Frans M.; Lampinen, Katja; Morin-Papunen, Laure; Bloemenkamp, Kitty W. M.; Kaaja, Risto J. (Thrombosis and Haemostasis, 2011)
Recurrent miscarriage affects 1–2% of women. In more than half of all recurrent miscarriage the cause still remains uncertain. Thrombophilia has been identified in about 50% of women with recurrent miscarriage and thromboprophylaxis has been suggested as an option of treatment. A randomised double-blind (for aspirin) multicentre trial was performed among 207 women with three or more consecutive first trimester (<13 weeks) miscarriages, two or more second trimester (13–24 weeks) miscarriages or one third trimester fetal loss combined with one first trimester miscarriage. Women were analysed for thrombophilia. After complete work-up, women were randomly allocated before seven weeks’ gestation to either enoxaparin 40 mg and placebo (n=68), enoxaparin 40 mg and aspirin 100 mg (n=63) or aspirin 100 mg (n=76). The primary outcome was live-birth rate. Secondary outcomes were pregnancy complications, neonatal outcome and adverse effects. The 0.92–1.48] was found for enoxaparin and placebo and 65% [RR 1.08, 95% CI 0.83–1.39] for enoxaparin and aspirin when compared to aspirin alone (61%, reference group). In the whole study group the live birth rate was 65% (95% CI 58.66–71.74) for women with three or more miscarriages (n=204). No difference in pregnancy complications, neonatal outcome or adverse effects was observed. No significant difference in live birth rate was found with enoxaparin treatment versus aspirin or a combination of both versus aspirin in women with recurrent miscarriage.
Keywords: Pregnancy; clinical trials; heparins/LMWH; thrombophilia